(untitled) (Bioagro, 2024)
We present the first registration of Puto barberi (Hemiptera: Putoidae) associated with the ornamental species Ixora coccinea L. in the city of Guayaquil, Ecuador. The symtoms of the attack are characterized by yellowing, necrosis and loss of the plant leaves.